Gender dalam Paradigma Sufisme - Abduh, Muhammad Arrafie (Research and Development Institution, Darussalam Institute for Islamic Studies, 2018)
This study aims to analyze gender issues in the Sufism paradigm. Through a study of relevant Sufism literature, this research has proven that Sufism paradigmatically views men and women as no different. In the eyes of God, according to the Sufis, the position of men and women (gender) is equal. The paradigm still recognizes the instinctive and instinctive differences between men and women with their respective strengths and weaknesses to give each other, receive and fill the void to reach al-insân al-kâmil (perfect human) on God's side. However, this article also finds that Sufi views on gender are not homogeneous. A number of Sufi figures examined in this article do have positive views towards women, but other Sufi figures may have different views. The difference between men and women from the view of Sufism is more emphasized on the outward aspect, while the inner aspect is essentially the same thing.